(untitled) (Heritage, 2025)
The aspects analyzed in this research tackle the challenges of the European Union normalization policy in the relationship between Belgrade and Pristina, requiring a two-level approach. In recent years, the EU’s normalization policy has primarily focused on the intergovernmental level, resulting in a series of agreements between Belgrade and Pristina across various sectors. However, the EU has largely overlooked the local context, as inter-ethnic dynamics remain burdened by numerous destabilizing factors and the further entrenchment of existing conflict structures. The disparity between the agreed solutions and the realities at the local level within the normalization policy is primarily observed in the socio-political domain of the Serbian population, particularly in northern Kosovo and Metohija. The paper analyzes the observed disproportion in the policy of normalization in the context of issues of the failure to establish the Association of Serbian municipalities. The research methodology employed in this study includes content analysis of relevant documents, discourse analysis and qualitative analysis of media content.